2015
DOI: 10.4103/0973-6247.154256
|View full text |Cite
|
Sign up to set email alerts
|

An acute hemolytic transfusion reaction due to the "anti-c" rhesus antibody: A case report emphasizing the role of transfusion medicine

Abstract: Rhesus (Rh) mediated hemolytic transfusion reactions (HTR) are usually immunoglobulin G mediated and delayed onset. Rh antibodies being the cause of acute HTR (AHTR) and intravascular hemolysis are still under debate. We report here a case of a 53-year-old male who developed AHTR due to “anti-c” antibodies within 3 h of blood transfusion, precipitating fatal acute liver failure in a patient with hepatitis C related chronic liver disease. This case emphasizes the need of inclusion of antibody screening in routi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…Curiously, certain Rh antibodies (particularly those with anti‐C specificity) have been described to cause delayed reactions associated with hemoglobinemia and hemoglobinuria. The pathophysiology of hemoglobinemia and hemoglobinuria in Rh antibody–mediated HTR has not been established …”
Section: Discussionmentioning
confidence: 99%
“…Curiously, certain Rh antibodies (particularly those with anti‐C specificity) have been described to cause delayed reactions associated with hemoglobinemia and hemoglobinuria. The pathophysiology of hemoglobinemia and hemoglobinuria in Rh antibody–mediated HTR has not been established …”
Section: Discussionmentioning
confidence: 99%
“…Many researchers found that the little c is the most prevalent and clinically significant RHantigen following D and cause delayed transfusion reactions and hemolytic disease of the new born [25][26][27].…”
Section: Plos Onementioning
confidence: 99%
“…Hemolytic complication of blood transfusion generally may be divided into two categories depending on the time of the appearance of the first symptoms: (1) Acute hemolytic transfusion reactions (AHTRs) and (2) delayed hemolytic transfusion reactions (DHTRs). AHTRs may occur within 24 hours after the transfusion of incompatible blood, while DHTRs occur due to the delayed antibody response from 24 hours up to months or years after transfusion of apparently compatible blood (1). Common reported non-ABO AHTRs are due to Kidd, Diego, and P antigens, etc.…”
Section: Introductionmentioning
confidence: 99%